1998
DOI: 10.1149/1.1838241
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Electrochemical Study of Copper Deposition onto Silicon from Dilute and Buffered Hydrofluoric Acids

Abstract: An electrochemical direct current polarization method was used to investigate characteristics of copper deposition onto silicon from dilute and buffered hydrofluoric acid solutions. The corrosion current density and corrosion potential of silicon were not very sensitive to the Cu2 concentration, up to 1000 parts per billion, in buffered hydrofluoric acid. However, the extent of copper deposition, as measured by total reflection X-ray fluorescence, increased as the Cu' concentration in solution increased. In di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
32
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 1 publication
2
32
0
Order By: Relevance
“…The reducing behavior of elemental silicon toward noble metal ions in aqueous solutions containing fluoride ions has long been known. Although the detailed mechanism by which metal ions are displaced from solution is still far from understood, the process is thought to be described by the following two half-cell reactions: where Me denotes any metal more noble than H (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…The reducing behavior of elemental silicon toward noble metal ions in aqueous solutions containing fluoride ions has long been known. Although the detailed mechanism by which metal ions are displaced from solution is still far from understood, the process is thought to be described by the following two half-cell reactions: where Me denotes any metal more noble than H (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, 8 we studied the phenomena of copper corrosion/dissolution during cleaning process, which led to the redeposition/precipitation of undesired copper and copper-rich residues onto the wafer surface, affecting the yield and reliability of devices. [9][10][11][12] The objective of the study reported herein is to investigate the kinetics of copper thin-film corrosion/dissolution in an aqueous solution containing HF and organic compounds and its relevance to the DD process of copper interconnects. Such solutions are commonly used in the industry for post-plasma-etch cleaning.…”
mentioning
confidence: 99%
“…In addition, many studies have also been carried out on the galvanic deposition of copper from fluoride containing solutions. [4][5][6][7][8][9][10][11] In contrast to electroless deposition, galvanic displacement deposition requires no prior activation of the surface and is truly selective to silicon surfaces. Thus, it provides an attractive deposition method for copper interconnects or seed layers for subsequent metallization.…”
mentioning
confidence: 99%
“…Independent of the substrates (i.e., p-or n-type, single-or polycrystalline silicon), the copper films exhibit a very high adhesion to the substrate and resistance to scratching, particularly compared to films obtained according to the published literature. [4][5][6][7][8][9][10][11] The particular structure of the copper film, likely due to the 3D growth, has a strong influence on the electrical resistivity of the films as deposited. Compared to a sputtered copper film on a titanium nitride seed layer, which exhibits resistivity of about 300 mΩ/ᮀ, the displaced copper as deposited is characterized by resistivity values over ten times higher.…”
mentioning
confidence: 99%